2020
DOI: 10.1523/jneurosci.1650-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

The Neuroimmunology of Chronic Pain: From Rodents to Humans

Abstract: Chronic pain, encompassing conditions, such as low back pain, arthritis, persistent post-surgical pain, fibromyalgia, and neuropathic pain disorders, is highly prevalent but remains poorly treated. The vast majority of therapeutics are directed solely at neurons, despite the fact that signaling between immune cells, glia, and neurons is now recognized as indispensable for the initiation and maintenance of chronic pain. This review highlights recent advances in understanding fundamental neuroimmune signaling me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
72
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(75 citation statements)
references
References 143 publications
3
72
0
Order By: Relevance
“…In support, we have previously shown that prior voluntary wheel running reduces DRG levels of ATF3, a marker of neuronal injury (Grace et al, 2016b). This proposal is also consistent with the sexually monomorphic anti-neuropathic function of Nrf2 (Rosa et al, 2008;Wang and Wang, 2017;Ferreira-Chamorro et al, 2018;Yang et al, 2018;Li et al, 2020;Grace et al, 2021). It is unknown whether Nrf2 is similarly engaged in reversal of established neuropathic pain by exercise (Cobianchi et al, 2010;Stagg et al, 2011;Li and Hondzinski, 2012;Groover et al, 2013;Benson et al, 2015;Bobinski et al, 2015;Grace et al, 2016b;Chhaya et al, 2019).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…In support, we have previously shown that prior voluntary wheel running reduces DRG levels of ATF3, a marker of neuronal injury (Grace et al, 2016b). This proposal is also consistent with the sexually monomorphic anti-neuropathic function of Nrf2 (Rosa et al, 2008;Wang and Wang, 2017;Ferreira-Chamorro et al, 2018;Yang et al, 2018;Li et al, 2020;Grace et al, 2021). It is unknown whether Nrf2 is similarly engaged in reversal of established neuropathic pain by exercise (Cobianchi et al, 2010;Stagg et al, 2011;Li and Hondzinski, 2012;Groover et al, 2013;Benson et al, 2015;Bobinski et al, 2015;Grace et al, 2016b;Chhaya et al, 2019).…”
Section: Discussionsupporting
confidence: 76%
“…Repeated bouts of exercise acutely increase ROS/RNS production by skeletal muscle and leukocytes, among other cells (Margaritelis et al, 2020). As an adaptive response, these species activate Nrf2 across both sexes, resulting in production of antioxidants (Done and Traustadottir, 2016;Grace et al, 2021). Such effects are apparent in our data, as prior voluntary wheel running also altered expression of antioxidants in shamoperated animals.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Neuropathic pain refers to pathological pain generated in response to lesion or disease of the somatosensory system (8). Given the varying etiologies and incompletely identified molecular mechanisms resulting in neuropathic pain, investigation into immune system involvement has received much attention (9,10). Whereas much of this focus has been directed to neuroimmune mechanisms within the damaged nerve, the dorsal root ganglia (DRG) and spinal cord, comparatively little is known regarding the cutaneous involvement in neuropathic pain sensation.…”
Section: Introductionmentioning
confidence: 99%
“…DMF also attenuated injury-induced increases in ROS and of proinflammatory cytokines in the dorsal root ganglia [53]. These actions are directly antinociceptive: reactive oxygen and nitrogen species induced after nerve injury hyperexcited sensory neurons via transient receptor potential ion channels, while inflammatory mediators enhance neuroexcitatory glutamatergic signaling in the pain neuraxis, among other mechanisms [57][58][59].…”
Section: Chronic Painmentioning
confidence: 96%